Stable isotopes (d13C, d18O) and LOI data from Lake Cubuk sediment core CK-1 - Faruk Ocakoğlu (PANGAEA, 2024)
The dataset contains stable isotope (d13C, d18O) and Loss on ignition (LOI) measurements derived from the sediment core CK-1, which was retrieved from Lake Cubuk, NW Anatolia, Turkey. The sediment core covers 300 cm depth and represents a 2800 year record. The main objective of the data analysis was to investigate regional climate dynamics and environmental variability by analysing multi-proxy tools and compare the results with other contemporaneous Anatolian climatic records.